The mandate and work of ICRP Committee 3 on radiological protection in medicine. (October 2018) - Miller, D.L.; Martin, C.J.; Rehani, M.M.
The mandate of Committee 3 of the International Commission on Radiological Protection (ICRP) is concerned with the protection of persons and unborn children when ionising radiation is used in medical diagnosis, therapy, and biomedical research. Protection in veterinary medicine has been newly added to the mandate. Committee 3 develops recommendations and guidance in these areas. The most recent documents published by ICRP that relate to radiological protection in medicine are 'Radiological protection in cone beam computed tomography' (ICRP Publication 129 ) and 'Radiological protection in ion beam radiotherapy' (ICRP Publication 127 ). A report in cooperation with ICRP Committee 2 entitled 'Radiation dose to patients from radiopharmaceuticals: a compendium of current information related to frequently used substances' (ICRP Publication 128 ) has also been published. 'Diagnostic reference levels in medical imaging' (ICRP Publication 135 ), published in 2017, provides specific advice on the setting and use of diagnostic reference levels for diagnostic and interventional radiology, digital imaging, computed tomography, nuclear medicine, paediatrics, and multi-modality procedures. 'Occupational radiological protection in interventional procedures' was published in March 2018 as ICRP Publication 139. A document on radiological protection in therapy with radiopharmaceuticals is likely to be published in 2018. Work is in progress on several other topics, including appropriate use of effective dose in collaboration with the other ICRP committees, guidance for occupational radiological protection in brachytherapy, justification in medical imaging, and radiation doses to patients from radiopharmaceuticals (an update to ICRP Publication 128 ). Committee 3 is also considering the development of guidance on radiological protection in medicine related to individual radiosusceptibility, in collaboration with ICRP Committee 1.